The perceived role of indigenous health practitioners in combating substance abuse at Mohodi Ga-Manthata in Limpopo Province - Khwinana, Kgothatso Glivance (My University, 2022)
Background: Substances abuse is affecting many young people in rural communities of Limpopo Province. There are no effective measures to combat substance abuse. Therefore, there is a need to strengthen substance abuse prevention and treatment services through the integration of indigenous health care practices. The Indigenous Health Practitioners Act No.22 of 2007 permits IHPs to provide prevention and treatment services to combat substance abuse. However, there is a lack of literature on the roles of IHPs in combating substance abuse. This paucity of literature necessitates the need to explore the perceived roles of IHPs in combating substance abuse. Objectives: The study aimed at exploring the perceived roles of IHPs in combating substance abuse at Mohodi Ga-Manthata in Limpopo Province. Method: A qualitative research approach using a case study design was conducted among IHPs of RDHA at Mohodi Ga-Manthata in Molemole Local Municipality of Limpopo Province. The purposive sampling technique was used in order to select IHPs that serve the aims of the study best to ensure that data saturation was reached. Data was collected through semi-structured one-to-one interviews with selected IHPs. Braun and Clarke’s six-phase framework for doing a thematic analysis was used to analyse data. An independent coder confirmed the findings. Results: The study findings revealed that IHPs perform demand reduction activities such as conducting awareness campaigns and involving young people in sporting and behavioural sessions for prevention of substance abuse. Furthermore, the findings show that IHPs perform harm reduction activities such as assessment and diagnosis, in-patient rehabilitation, counselling, diet therapy and prescription of indigenous medicines for treatment of substance abuse. Conclusion: The Indigenous Health Practitioners Act No.22 of 2007 permits IHPs to provide prevention and treatment services to combat substance abuse. The current study shows that IHPs have a significant role in demand reduction, harm reduction and supply reduction of substance abuse in rural communities. Therefore, there is a need for the Departments of Health and Department of Social Development to develop strategies to effectively train and integrate IHPs into the health system to ensure the provision of quality substance abuse continuum of care services and the strengthening of the health system.
Thesis (MPH.) -- University of Limpopo, 2022
Keywords: Perception; Role; Indigenous Health Practitioner; Substance abuse; Combating substance abuse; Substance abuse; Substance abuse -- Alternative treatment; Indigenous peoples -- Health and hygiene